Grand Push Auto: a car based exertion game - Marshall, Joe; Loesche, Frank; Linehan, Conor; Johnson, Daniel; Martelli, Bruno (2015)
Grand Push Auto is an exertion game in which players aim to push a full sized car to ever increasing speeds. The re-appropriation of a car as essentially a large weight allows us to create a highly portable and distributable exertion game in which the main game element has a weight of over 1000 kilograms. In this paper we discuss initial experiences with GPA, and present 3 questions for ongoing study which have been identified from our early testing: How might we appropriate existing objects in exertion game design, and does appropriation change how we think about these objects in different contexts, for example environmental awareness? How does this relate to more traditional sled based weight training? How can we create exertion games that allow truly brutal levels of force?